// End script hiding -->
SOLUTION: factor completely: -36m^2 + 6m + 12
Algebra
->
Polynomials-and-rational-expressions
-> SOLUTION: factor completely: -36m^2 + 6m + 12
Log On
Ad:
Mathway
solves algebra homework problems with step-by-step help!
Algebra: Polynomials, rational expressions and equations
Section
Solvers
Solvers
Lessons
Lessons
Answers archive
Answers
Immediate math help from PAID TUTORS
. (paid link)
Click here to see ALL problems on Polynomials-and-rational-expressions
Question 614323
:
factor completely: -36m^2 + 6m + 12
Answer by
jim_thompson5910(33401)
(
Show Source
):
You can
put this solution on YOUR website!
Start with the given expression.
Factor out the GCF
.
Now let's try to factor the inner expression
---------------------------------------------------------------
Looking at the expression
, we can see that the first coefficient is
, the second coefficient is
, and the last term is
.
Now multiply the first coefficient
by the last term
to get
.
Now the question is: what two whole numbers multiply to
(the previous product)
and
add to the second coefficient
?
To find these two numbers, we need to list
all
of the factors of
(the previous product).
Factors of
:
1,2,3,4,6,12
-1,-2,-3,-4,-6,-12
Note: list the negative of each factor. This will allow us to find all possible combinations.
These factors pair up and multiply to
.
1*(-12) = -12
2*(-6) = -12
3*(-4) = -12
(-1)*(12) = -12
(-2)*(6) = -12
(-3)*(4) = -12
Now let's add up each pair of factors to see if one pair adds to the middle coefficient
:
First Number
Second Number
Sum
1
-12
1+(-12)=-11
2
-6
2+(-6)=-4
3
-4
3+(-4)=-1
-1
12
-1+12=11
-2
6
-2+6=4
-3
4
-3+4=1
From the table, we can see that the two numbers
and
add to
(the middle coefficient).
So the two numbers
and
both multiply to
and
add to
Now replace the middle term
with
. Remember,
and
add to
. So this shows us that
.
Replace the second term
with
.
Group the terms into two pairs.
Factor out the GCF
from the first group.
Factor out
from the second group. The goal of this step is to make the terms in the second parenthesis equal to the terms in the first parenthesis.
Combine like terms. Or factor out the common term
--------------------------------------------------
So
then factors further to
===============================================================
Answer:
So
completely factors to
.
In other words,
.
Note: you can check the answer by expanding
to get
or by graphing the original expression and the answer (the two graphs should be identical).
--------------------------------------------------------------------------------------------------------------
If you need more help, email me at
jim_thompson5910@hotmail.com
Also, please consider visiting my website:
http://www.freewebs.com/jimthompson5910/home.html
and making a donation. Thank you
Jim
--------------------------------------------------------------------------------------------------------------